The Effect of Clean Water Facilities and Household Food Sanitation Hygiene on Stunting in Toddlers - Samuel Marganda Halomoan Manalu; Deli Syaputri; Th. Teddy Bambang S; Nelson Tanjung; Risnawati Tanjung; Adisyah Putra Damanik (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
Stunting is a linear growth disorder of a child's body that becomes short or short based on height for age with a Z-score threshold of < -2 standard deviations. Multi-dimensional factors, including environmental factors, cause stunting. Environmental factors that cause stunting are the mother's personal hygiene, sanitation, clean water and drinking water sources. This study aimed to determine the effect of clean water sanitation facilities and household food sanitation hygiene on stunting in toddlers. Observational study with a case-control design in children aged 0-59 months in Silahisabung District, Dairi Regency. The population used in this research is 453 toddlers aged 0-59 months. Case sampling technique using total sampling. All stunting toddlers were taken as cases of 78 toddlers and 78 as controls. Using weight scales and body length measuring instruments, research data was collected using questionnaires and tools to determine the nutritional status of babies under two years old. Data processing and analysis included univariate and bivariate using the chi-square test. The results showed that there were stunted toddlers, namely 61.5% did not have access to water facilities that met the requirements, and 44.9% of toddlers who suffered from stunting were in the age range of 21-40 months. Bivariate analysis using the chi-square test showed an effect of clean water sanitation (p=0.002, OR=2.764) and household food sanitation hygiene (p=0.004, OR=2.562) on the incidence of stunting in toddlers. Management of stunting events requires good coordination and collaboration between health workers, the government and the community in reducing risk factors. Personal hygiene will be further improved in preparing and processing food by practising the principles of food sanitation hygiene.Keywords: Food Hygiene, Sanitation, Stunting, Toddlers